2021
DOI: 10.3201/eid2701.201543
|View full text |Cite
|
Sign up to set email alerts
|

Territorywide Study of Early Coronavirus Disease Outbreak, Hong Kong, China

Abstract: Initial cases of coronavirus disease in Hong Kong were imported from mainland China. A dramatic increase in case numbers was seen in February 2020. Most case-patients had no recent travel history, suggesting the presence of transmission chains in the local community. We collected demographic, clinical, and epidemiologic data from 50 patients, who accounted for 53.8% of total reported case-patients as of February 28, 2020. We performed whole-genome sequencing to determine phylogenetic relationship and transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Lockdown and travel restriction measures have varied from country to country, which has dictated the profile of local outbreaks. Through the sharing of SARS-CoV-2 sequences during this pandemic, including from one of the first cases in Wuhan, China (MN908947.3) 7 , genomic epidemiology investigations are playing a major role in characterizing and understanding this emerging virus [8][9][10][11][12][13] . SARS-CoV-2 has typically been classified into two main phylogenetic lineages: lineage A and lineage B.…”
mentioning
confidence: 99%
“…Lockdown and travel restriction measures have varied from country to country, which has dictated the profile of local outbreaks. Through the sharing of SARS-CoV-2 sequences during this pandemic, including from one of the first cases in Wuhan, China (MN908947.3) 7 , genomic epidemiology investigations are playing a major role in characterizing and understanding this emerging virus [8][9][10][11][12][13] . SARS-CoV-2 has typically been classified into two main phylogenetic lineages: lineage A and lineage B.…”
mentioning
confidence: 99%
“…An epidemiological study showed that the cases of 8V were involved in two clusters, “Hotpot dinner gathering at Kwun Tong,” and “Fook Wai Ching She in Maylun Apartments in North Point.” 11 A research group in Hong Kong also detected the 8V viruses for the 50 viruses collected before March 2020. The 8V viruses accounted for 54% of genomes sequenced (27/50) 12 . The 12F was detected from July to September 2020, it coincided with the peak observed during July 2020.…”
Section: Discussionmentioning
confidence: 80%
“…For WGS of SARS-CoV-2, human DNA was removed from the RNA elutes with the use of Turbo DNA-free Kit (ThermoFisher Scientific, Waltham, MA, USA) [ 8 ]. cDNA was synthesized by using LunaScript RT SuperMix Kit (New England BioLabs Inc. (NEB), Hitchin, UK) and was then amplified by multiplex PCR with Q5 Hot Start High-Fidelity 2X Master Mix Kit (NEB) and ARTIC nCoV-2019 V3 primer sets (Integrated DNA Technologies, Coralville, IA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Sequencing data were analysed by using the pipelines modified from the ARTIC network nCoV-2019 novel coronavirus bioinformatics protocol [ 8 , 9 ]. In brief, filtered reads with length between 400 and 700 bp were mapped to the reference genome Wuhan-Hu-1 (GenBank no.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation